The Effect of Moist Feeding with Different Dosages of Probiotic on the Growth of Sand Lobster (Panulirus homarus) in Floating Cages - Sumiati; Muhammad Junaidi; Andre Rahmat Scabra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Lobsters are carnivorous (meat-eating) animals, one of the main types of feed used in lobster cultivation is trash fish. Trash fish has a protein content of 84.67% on dry weight and 18.78 on wet weight. The purpose of this study was to determine the growth of sand lobsters (Panulirus homarus) by providing moist feed and adding different doses of probiotics. This study used the RAL method (completely randomized design) with 6 treatments and 3 replications. The study was conducted for 60 days using sand lobsters measuring 3 cm in length and weighing 2 grams/head, then reared in KJA. The results showed that the use of wet feed with the addition of probiotics in this study had a significant effect on the growth of sand lobsters. The best probiotic dose obtained was 3% in the P2 treatment (wet feed + 3% probiotics). The absolute weight and length are 91.23 grams and 4.19 cm; Specific gravity and length 1.74 grams and 1.46 cm; SR of 81.33%; FCR of 7.60 ; Feed efficiency 91.30%; and protein retention of 28.86%. The growth of sand lobsters continued to decline along with the high doses of probiotics given. Giving probiotics with different doses is thought to affect the value of protein in feed. Laboratory test results showed that the protein value continued to decrease along with the high doses of probiotics given. The author suggests using different types of probiotics to determine the type and effective dosage for the growth of sand lobsters.